The Mundell-Fleming Model: A Dirty Float Version - Mendoza, Waldo (Pontificia Universidad Católica del Perú. Departamento de Economía, 2019)
A popular model in the teaching of macroeconomics of open economies at the undergraduate level is the Mundell-Fleming (MF). This model assumes that there is free capital mobility and takes into account two extreme exchange rate regimes: fixed and freely floating. But there is a third regime, currently of relevance to many central banks, which is not addressed in the MF: one in which the central bank sets the short-term interest rate and maintains a dirty-float exchange-rate regime. In this paper, an MF with these characteristics is presented. It is a simple, practical and userfriendly model that can be used to address contemporary issues, making it suitable for central banks or the teaching of macroeconomics at undergraduate level as a complement ―or even a substitute― for the traditional MF.
Documento de trabajo; 477
Keywords: Mundell-Fleming; Dirty float; Imperfect; Capital mobility; http://purl.org/pe-repo/ocde/ford#5.02.00